2021
DOI: 10.1002/advs.202103038
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Diffusion‐Driven Ionovoltaic Transducer for Probing Ion‐Molecular Interactions at Solid–Liquid Interface

Abstract: Ion-solid surface interactions are one of the fundamental principles in liquid-interfacing devices ranging from various electrochemical systems to electrolyte-driven energy conversion devices. The interplays between these two phases, especially containing charge carriers in the solid layer, work as a pivotal role in the operation of these devices, but corresponding details of those effects remain as unrevealed issues in academic fields. Herein, an ion-charge carrier interaction at an electrolyte-semiconductor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…A possible explanation of the generation of electricity during water evaporation is related to the ionovoltaic effect, 12,15,16 where ionic movement is coupled with movement of charge carriers in the conductive (GNP) phase of the device, as shown in Fig. 5a and S12 ‡.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation of the generation of electricity during water evaporation is related to the ionovoltaic effect, 12,15,16 where ionic movement is coupled with movement of charge carriers in the conductive (GNP) phase of the device, as shown in Fig. 5a and S12 ‡.…”
Section: Resultsmentioning
confidence: 99%
“…As ionic movement in the aqueous phase combined with interfacial ion–charge carrier interactions lead to movement of charge carriers in the conductive phase (providing a voltage) this type of process may appropriately be labeled as an ionovoltaic process. 8,12,15–17 It should be noted that similar processes have been labeled as hydrovoltaics in many recent publications, even though ionic species often are involved in the operating mechanisms. Regardless of the choosen label, this approach has recently received much interest; for example, by employing carbonaceous materials such as carbon nanotubes and graphene as electrically conductive phase.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, ion-based stretchable electronics have received intensive attention due to the potential uses in deformable physical sensors to monitor strain, 1,2 touch, 3,4 pressure, 5,6 temperature, 7,8 and biological chemical changes. 9 Delicate synaptic control is expected to be achieved by the ionovoltaic signal generation 10 and the organic electrochemical transistors (OECTs). 11−13 However, the moisture dependence of the ion properties is a challenging drawback of the ion gelbased sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Over the past decade, ion-based stretchable electronics have received intensive attention due to the potential uses in deformable physical sensors to monitor strain, , touch, , pressure, , temperature, , and biological chemical changes . Delicate synaptic control is expected to be achieved by the ionovoltaic signal generation and the organic electrochemical transistors (OECTs). However, the moisture dependence of the ion properties is a challenging drawback of the ion gel-based sensors. , The impedance of the ion gel can shift down under high relative humidity (RH) or under a water environment. This humidity dependence results from the intrinsic property changes such as the bulk conductivity (σ) and permittivity (ε). , Although Kim et al recently demonstrated that maintaining the ion gel layer in a water-saturated state can effectively eliminate the moisture dependence of the electrochemical performance of ion gel, complete water passivation is conventional and immediately applicable to a wide range of stretchable devices.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies on the water motion active transducer using a dielectric layer and a hydrophobic layer show that the dielectric constant of the dielectric layer determines the amount of energy harvested . The ion–solid interactions and the solid–liquid interfacial potentials determine the output voltage driven by the macroscopic water motion. The primary mechanism of this process is dependent on the reversible hydration and dehydration of the materials. The preformed ionizable groups with gradient distribution release out hydrated ions when exposed to moisture.…”
mentioning
confidence: 99%